Considering the availability of cold bridges in the design of thermal insulation shell of sandwich panels element-by-element assembly (Academic journal Industrial Machine Building Civil Engineering, 2020)
The work is devoted to the refinement of engineering methods for calculating heat loss through structures made of prefabricated sandwich panels. At buildings installation in places of steel structures adjunction "cold bridges" and, as a result, condensate and mildew are formed. Heat loss due to "cold bridges" can reach up to 50% of the total house heat loss and affect its energy efficiency class. The paper presents typical energy-efficient structural units of enclosing structures made of sandwich panels and the results of these nodes temperature field modelling, which allow by the DSTU ISO 10211: 2005 method to determine the linear heat transfer coefficients, which can be used in engineering calculations of relevant structures transfer resistance and supplement Annex G in DSTU B V.2.6-189: 2013.  Calculation of the linear coefficient of thermal conductivity for different variants of structures adjacency will avoid thermal failures and increase the energy efficiency class of buildings
Keywords: heat loss; insulation; linear heat transfer coefficients; temperature field